Prevalence of Brain and Neck Neoplasms among Interventional Cardiologists; A Multicenter Study - Tariq, Muhammad Naeem; Samore, Naseer Ahmed; Rashid, Muhammad Humayoun; Tuyyab, Farhan; Ali, Jahanzab; Ahmed, Iftikhar; Khan, Muhammad Nadir; Noeman, Ahmad; Chaudhery, Ghoza; Farhan, Shaheer (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the prevalence of brain and neck neoplasms among Interventional Cardiologists. Study Design: Analytical Cross-sectional study. Place and Duration of Study: Department of Cardiology/Interventional Cardiology of two Tertiary Cardiac Care Centers of Rawalpindi and Lahore Pakistan from Mar 2021 to Apr2022. Methodology: By using the non-probability, consecutive sampling technique, fifty Interventional Cardiologists’ (n=50) of both genders between 35-75 years of age, working in the cardiac catheterization labs for more than 10-years are enrolled after their informed consents. The data was collected from the interviews of Interventional cardiologists, from the shared medical records and also from the family members and colleagues. The Interventional cardiologists were enquired about any neurological signs and symptoms particularly in relation to the head and neck malignancy and also asked about undergoing any CT/MRI or PET scan of head and neck region in the past or recent time. Descriptive statistics for data was computed byusing the SPSS version-25. Results: The mean age of the Interventional Cardiologists of tertiary cardiac care center of Rawalpindi was 50.40±7.77years while of Lahore was 49.16±8.89 years. There were 47(94.0%) males and 03(6.0%) females, from both the Institutes. The mean duration of working in cardiac catheterization labs was 17.92±4.57 years. The head and neck neoplasm’s among Interventional Cardiologists was observed in 01(2%) case. Conclusion: The research study concluded that the prevalence of head and neck neoplasms among Interventional Cardiologists is very low (2%). But still it is the need of hour to be more careful about radiation exposure among the Interventional Cardiologists working for long hours in the cardiac catheterization labs, to lessen down the chances of head and neck malignancy.